New composition for insecticides - Kassim, Nur Kartinee; Amin, Ismail; Mat Ali @ Ibrahim, Mohd Shukri; Garba, Jamila (2023)
The present invention relates to a new formulation and application of the product for insecticide, that is effective in controlling agricultural insects including Spodoptera litura and Crocidolomia binotalis and more particularly relates to an insecticidal composition that contains epoxy-linalooloxide, isopropyl 4-methy-3-methylene-4-pentenoate, nerolic acid, and citral such that the insectidal composition is an effective anti-feedant and larvicide but is non toxic to humans, animals, and the environment.